Determinants of myocardial fibrosis in patients with immune-mediated inflammatory diseases - Nicholas Black; Joshua Bradley; Fardad Soltani; John P. Farrant; Josephine H. Naish; Matthias Schmitt; Maya H. Buch; Christopher A. Miller (Advances in Rheumatology)
Abstract Background Myocardial fibrosis is an important adverse prognostic marker, however; determinants of myocardial fibrosis in immune-mediated inflammatory diseases (IMIDs) remain poorly defined. We aimed to identify determinants of myocardial fibrosis in patients with IMIDs, as measured by cardiovascular magnetic resonance (CMR) extracellular volume (ECV). Methods Cross-sectional study of 116 patients with IMIDs undergoing clinical CMR at Manchester University NHS Foundation Trust. IMIDs included rheumatoid arthritis, systemic lupus erythematosus, systemic sclerosis (SSc), ankylosing spondylitis, psoriatic arthritis and vasculitis. CMR included pre- and post-contrast T1 mapping to measure myocardial ECV, with same day blood sampling. Determinants of ECV were investigated with univariable and multivariable linear regression. Results ECV varied significantly according to IMID diagnosis (ANOVA F statistic 2.80, P = 0.015); ECV was higher in patients with SSc compared to other IMIDs. Major determinants of ECV as a continuous variable were SSc, smoking and body mass index (BMI); regression coefficients 3.33 (95% confidence interval 0.82–5.84), 3.08 (0.73–5.43), and − 0.19 (-0.29 – -0.09) respectively, P < 0.01 (SSc, smoking and lower BMI were associated with increased ECV). Approximately a quarter of the variability in ECV could be explained by these predictors (optimism adjusted R2 0.265). Conclusion SSc is associated with a higher burden of myocardial fibrosis compared to other IMIDs. In patients with IMIDs, independent determinants of myocardial fibrosis were presence of SSc, smoking and BMI. Importantly, participants underwent CMR for clinical indications and may not be representative of IMID populations in the community.